2022
DOI: 10.1038/s41467-022-33501-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enantioselective chiral covalent organic frameworks and cysteine sacrificial donors on photocatalytic hydrogen evolution

Abstract: Covalent organic frameworks (COFs) have constituted an emerging class of organic photocatalysts showing enormous potential for visible photocatalytic H2 evolution from water. However, suffering from sluggish reaction kinetics, COFs often cooperate with precious metal co-catalysts for essential proton-reducing capability. Here, we synthesize a chiral β-ketoenamine-linked COF coordinated with 10.51 wt% of atomically dispersed Cu(II) as an electron transfer mediator. The enantioselective combination of the chiral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 56 publications
1
53
0
Order By: Relevance
“…The performance FE CO of CoPc-DSDS-COF catalysts at 10 mA cm –2 current density is better than that of most COF catalysts reported so far, such as COF-Co-366 (FE CO 90%) 4 , COF-Co-367 (FE CO 91%) 4 , Co-TTCOF (FE CO 91.3%) and CuPcF8-CoPc-COF (FE CO 91%) . CoPc-DSDS-COF and CoPc-DNDS-COF delivered the highest j CO values of 30.42 and 19.6 mA cm –2 at −1.0 V (Figure S17 red and blue curves).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The performance FE CO of CoPc-DSDS-COF catalysts at 10 mA cm –2 current density is better than that of most COF catalysts reported so far, such as COF-Co-366 (FE CO 90%) 4 , COF-Co-367 (FE CO 91%) 4 , Co-TTCOF (FE CO 91.3%) and CuPcF8-CoPc-COF (FE CO 91%) . CoPc-DSDS-COF and CoPc-DNDS-COF delivered the highest j CO values of 30.42 and 19.6 mA cm –2 at −1.0 V (Figure S17 red and blue curves).…”
mentioning
confidence: 80%
“…Covalent organic frameworks (COFs) are an emerging class of crystalline porous material with structural regularity, simple accessibility, chemical stability, and built-in functional tunability at the molecular level. To date, many COFs have been synthesized and have shown great potential for applications in various fields such as gas separation and storage, optoelectronics, energy storage, and catalysis. Among all COFs, owing to the photosensitive 18π aromatic macrocyclic nature of MPc, constructing COFs with MPc units provides an opportunity for the development of electrochemical materials and has recently become a hot research topic. In 2021, two novel pyrazine (pz)-linked metal-phthalocyanine (MPc)-based conjugated 2D COFs were constructed by the Feng group . Most relevantly, Jiang et al reported that phenazine-linked Co-phthalocyanine COFs (CoPc-PDQ-COFs) with high stability and conductivity were used as efficient electrocatalysts for the CO 2 RR .…”
mentioning
confidence: 99%
“…By contrast, pore-forming materials were regarded as one brilliant choice to improve mass transfer. [43,44] covalent organic frameworks (COFs), [45] an emerging material with regular pores and good crystallinity, are widely used in catalysis, energy conversion, and gas storage, [46][47][48][49][50] and it is constructed by light elements through covalent bonds, which has the advantages of higher stability and lower density than the metal-organic frameworks that formed by coordination of metal ions or clusters with organic ligands. Moreover, COFs are composed of topologically connected organic building units, [51,52] functional groupsThe establishment of abundant three-phase interfaces with accelerated mass transfer in air cathodes is highly desirable for the development of high-rate and long-cycling rechargeable zinc-air batteries (ZABs).…”
mentioning
confidence: 99%
“…For instance, Pt-coordinated imine-linked COFs or alkene-linked COFs show good photocatalytic performance. [13][14][15] However, COFs still suffer from an amorphous structure and chemical instability. COFs synthesized by Schiff base reaction or boronic acid dehydration reaction can achieve high crystallinity at the expense of charge carrier mobility, due to poor electron delocalization caused by the strongly polarized nature of the dynamic covalent bonds.…”
mentioning
confidence: 99%
“…For instance, Pt-coordinated imine-linked COFs or alkene-linked COFs show good photocatalytic performance. 13–15…”
mentioning
confidence: 99%